Efeito do óleo de peixe e da gordura de coco associada ao estresse pré-natal sobre o desenvolvimento pós-natal e a resposta comportamental e de corticosterona da prole na idade adulta - Borsonelo, Elizabethe Cristina [UNIFESP] (2010)
Adequate development of the central nervous system depends on prenatal and postnatal factors. On one hand, prenatal stress (PNS) has been implicated in impaired development of the offspring. On the other hand, nutritional factors during pregnancy and lactation can influence fetal and postnatal growth. This study assessed the postnatal development of rat offspring exposed to PNS whose mothers were fed with different diets during pregnancy and lactation. Female Wistar rats were assigned to one of three groups: regular diet, diet supplemented with coconut fat or fish oil. When pregnancy was confirmed, they were distributed into control (CTL) or PNS (daily restraint stress during the last week of pregnancy) groups. . Body weight, righting reflex, eye opening and locomotion were assessed during different phases of development. Maternal corticosterone levels were determined throughout the experimental period: two days before PNS (baseline) and immediately after the stress sessions on days 14 and 21 of pregnancy. The depressive–like behavior in the forced swimming test and corticosterone levels were measured in the adult male offspring exposed to PNS. Maternal weight gain was impaired by PNS. Corticosterone levels were higher in PNS groups compared to the control group. At birth, PNS males and females weighted less than those on the group CTL. At 21 days of age, PNS males and females fed the regular diet had lower body weight than their respective CTL and coconut fat, but fish oil prevented this effect. PNS increased the latency of righting reflex at day 1 of age, and this impairment was prevented by coconut fat-supplemented diet. However, fish oil impaired the righting reflex in CTL males. PNS induced hyperactivity in 13 day-old male and female pups, and this effect was prevented by fish oil supplementation only in females. In the adulthood, PNS rats showed lower body weight than control. However, the immobility time was lower in PNS than in control rats. After the forced swimming test, plasma corticosterone levels were decreased in PNS fed regular diet compared to control in same diet. No differences were observed with either diet on body weight or immobility behavior. However, the corticosterone levels were modified by early fish oil or coconut fat supplement. The corticosterone response was also lower in control rats whose mothers were fed diets supplemented with fish oil or coconut fat than regular diet. In conclusion, postnatal development from birth to weaning was influenced by PNS and diet and some of the alterations induced by PNS were prevented by coconut fat and fish oil. These data support the idea that PNS causes long-term consequences in adulthood. Furthermore, both manipulations, PNS and supplemented diets, influenced the corticosterone response in adulthood.